2012
DOI: 10.1093/jac/dks014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interference of tigecycline at subinhibitory concentrations on biofilm development by Enterococcus faecalis

Abstract: In vitro tigecycline subinhibitory concentrations were able to interfere with biofilm formation by E. faecalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…Tigecycline has previously been reported to inhibit biofilm formation in enterococci. Maestre and colleagues demonstrated that tigecycline decreased the adherence of 55% of the isolates that had strong biofilm-formation ability 39 . To the best of our knowledge, there are no published reports of biofilm inhibition by vancomycin in enterococci, but there is a precedent case reported for a clinical staphylococcal isolates 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline has previously been reported to inhibit biofilm formation in enterococci. Maestre and colleagues demonstrated that tigecycline decreased the adherence of 55% of the isolates that had strong biofilm-formation ability 39 . To the best of our knowledge, there are no published reports of biofilm inhibition by vancomycin in enterococci, but there is a precedent case reported for a clinical staphylococcal isolates 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The selected microorganisms are responsible for >95% of infections related with permanent devices used in clinical practices. All strains were purchased from American Type Culture Collection and were strong biofilm producers as determined spectrophotometrically by the crystal violet staining method [26,27] on polystyrene flat-bottom 96-well microtiter plates (Greiner bio-one, Kremsmünster, Austria) (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Subinhibitory antibiotic concentrations have been shown to affect the physioelectrical (34) and adhesion (35) behavior of E. faecalis. In addition, low concentrations of tigecycline have been shown to reduce biofilm formation even when the growth of planktonic cells is not significantly affected (36). To our knowledge, however, this is the first work to describe enhancement of biofilm formation by E. faecalis due to cell wall synthesis inhibitors.…”
Section: Discussionmentioning
confidence: 85%